New roles of N6-methyladenosine methylation system regulating the occurrence of non-alcoholic fatty liver disease with N6-methyladenosine-modified MYC - Cheng, Wenli; Li, Min; Zhang, Luyun; Zhou, Cheng; Yu, Susu; Peng, Xinyue; Zhang, Wenji; Zhang, Wenjuan (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) has become a major chronic disease in contemporary society, affected by N6-methyladenosine (m6A) RNA methylation, one of the most common RNA modifications. Compared with healthy control, m6A RNA methyltransferase 3 (METTL3) and METTL14 increased, while Wilms tumor 1-associated protein (WTAP) and RNA-binding motif protein 15 (RBM15) decreased significantly in NAFLD, and the m6A demethylases fat mass and obesity-associated protein (FTO) elevated. Meanwhile, the m6A binding proteins, YT521-B homology (YTH) domain-containing 1 (YTHDC1), YTHDC2, insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1), heterogeneous nuclear ribonucleoprotein C (HNRNPC) and HNRNPA2B1 were decreased, while eukaryotic translation initiation factor 3 subunit H (EIF3H) was increased significantly. All changes above of m6A regulators had significant differences between healthy control and NAFLD, but no differences between the NAFL and NASH group. The expression level of RBM15, HNRNPC and HNRNPA2B1 were related to body fat index. The RBM15, YTHDC2, HNRNPC, HNRNPA2B1 and EIF3H were related to steatosis. And the KIAA1429 and YTH domain family 1 (YTHDF1) were related to lobular inflammation. Taken together, m6A regulators were involved in the occurrence of NAFLD. More importantly, abnormal MYC was determined as a key link to m6A regulation of NAFLD. The higher MYC mRNA level was accompanied by the higher HDL cholesterol and unsaturated fatty acids proportions, as well as the lower fatty, glucose and transaminase. Taken together, dysregulation of m6A methylation caused steatosis and fibrosis, affecting the occurrence of NAFLD, and MYC might be its potential target.